Correlation of Nitrite and Ammonia with Prevalence of Enterocytozoon hepatopenaei (EHP) in Shrimp (Litopenaeus vannamei) on Several Super-Intensive Ponds in East Java, Indonesia - Anord Charles Nkuba; Gunanti Mahasri; Nunuk Dyah Retno Lastuti; Adamu Ayubu Mwendolwa (Jurnal Ilmiah Perikanan dan Kelautan)
Abstract